Soil microbiome bacteria protect plants against filamentous fungal infections via intercellular contacts - Long Lin; Danyu Shen; Xiaolong Shao; Yicheng Yang; Li Li; Caihong Zhong; Jiandong Jiang; Mengcen Wang; Guoliang Qian (Proceedings of the National Academy of Sciences, 2025)
Bacterial–fungal interaction (BFI) has significant implications for the health of host plants. While the diffusible antibiotic metabolite-mediated competition in BFI has been extensively characterized, the impact of intercellular contact remains largely elusive. Here, we demonstrate that the intercellular contact is a prevalent mode of interaction between beneficial soil bacteria and pathogenic filamentous fungi. By generating antibiotics-deficient mutants in two common soil bacteria, Lysobacter enzymogenes and Pseudomonas fluorescens , we show that antibiotics-independent BFI effectively inhibits pathogenic fungi. Furthermore, transcriptional and genetic evidence revealed that this antibiotics-independent BFI relies on intercellular contact mediated by the type VI secretion system (T6SS), which may facilitate the translocation of bacterial toxic effectors into fungal cells. Finally, by using a “conidia enrichment” platform, we found that T6SS-mediated fungal inhibition resulting from intercellular contact naturally occurs within the soil microbiome, particularly represented by Pseudomonas fulva . Overall, these results demonstrate that bacteria from the soil microbiome can protect host plants from fungal infection through antibiotics-independent intercellular contacts, thus revealing a naturally occurring and ecologically important mode of BFI in agricultural contexts.